PRODUKSI KITOSAN SECARA ENZIMATIK OLEH Bacillus firmus E65 UNTUK PENGENDALIAN PENYAKIT ANTRAKNOSA PADA BUAH MANGGA (Mangifera Indica L.) - Dwina Mulyaningtyas; Susiana Purwantisari; Endang Kusdiyantini; Yadi Suryadi (Jurnal Akademika Biologi, 2016)
Anthracnose is postharvest disease on mango caused by fungi Colletotrichum gloesporioides. Anthracnose can be inhibited development by chitosan as a preservative anti-fungal for fruit. Effectiveness of chitosan can be increased by enzymatic hydrolyze method to obtain a low molecular weight chitosan. Low molecular weight chitosan can be reducing the particle size into nano chitosan. This study aims to obtain the low molecular weight of chitosan by hydrolyzing the commercial chitosan enzymatically using B. firmus E65, the production of nano chitosan with ionic gelation method and to determine the volume ratio of low molecular weight of chitosan and natrium tripolifosfat (NaTPP) to conduct in vitro and in vivo inhibition on the growth of fungi C. gloeosporioides. The method consist of the production of chitinase from B. firmus E65, the production chitinase of low molecular weight chitosan, ionic gelation, in vitro and in vivo nanochitosan bioassay test on the growth of C. gloeosporioides. The research result showed that the activity of  the crude extract of chitinase is 0.05 U/mL and the purity is 0.07 U/mL. The spesific activity value of crude extract is 0.44 U/mg, and the purity is 0.82 U/mg. The purity level of crude extract is increased 0.83 times from 1 to 1.83 times after purification process. Molecular weight of enzimatically hydrolyzed chitosan is  511.850 Kda. In vitro and in vivo bioassay showed the best result on the growth of C. gloeosporioides are 90 and 91% is obtained in the combination 3:1 of the low molecular weight chitosan and NaTTP. This comparison showed that the size of nano chitosan is 228.74 and the polidispesity index is 0.884. Keywords : Chitinase, chitosan, B, firmus E65, antrachnose, C. gloesporioides.